Transformasi Mindset Berfikir dalam Pendidikan Agama Islam untuk Meningkatkan Kreativitas Mahasiswa - Sodikin (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This study aims to analyze the transformation of mindset in Islamic Religious Education (PAI) and its role in fostering students' creative thinking. The research explores how curriculum development and innovative learning strategies can enhance students' ability to think critically and innovatively. A qualitative research approach with a case study method was employed, focusing on the Master's Program in Islamic Religious Education at the International Islamic University Darullughah Wadda'wah. Data were collected through observations, in-depth interviews, and document analysis, which were then thematically analyzed to identify patterns in mindset transformation and creativity development. The findings indicate that integrating bayani, burhani, and irfani reasoning in PAI significantly enhances students’ ability to engage in higher-order thinking processes. The use of experiential learning models, such as problem-based learning (PBL) and project-based learning (PjBL), has proven effective in encouraging intellectual curiosity and innovative problem-solving skills. Theoretical perspectives from Ibn Khaldun, Al-Farabi, Al-Jabiri, and Al-Attas suggest that the integration of religious sciences with modern knowledge is essential for developing a dynamic and adaptive educational framework. However, institutional rigidity and resistance to pedagogical innovation remain key challenges. The study concludes that PAI must move beyond rote memorization by adopting transformative learning strategies that foster creativity and critical thinking. A curriculum that harmonizes religious values with contemporary knowledge provides a strong foundation for producing graduates who are not only spiritually grounded but also intellectually and creatively empowered to address modern challenges.